Discovery of Disulfane (H2S2) in Fluid Inclusions in Rubies from Yuanjiang, China, and Its Implications - Wenqing Huang; Pei Ni; Jungui Zhou; Ting Shui; Junying Ding; Renzhi Zhu; Yitao Cai; Mingsen Fan (Crystals, 2021)
Raman spectra of fluid inclusions in gem rubies from Yuanjiang deposit (China) within the Ailao Shan-Red River (ASRR) metamorphic belt showed the presence of compounds such as CO2, COS, CH4, H2S, and elemental sulfur (S8), accompanied by two bands at approximately 2499 and 2570 cm−1. These two frequencies could be assigned to the vibrations of disulfane (H2S2). This is the second case of the sulfane-bearing fluid inclusions in geological samples reported, followed by the first in quartzite from Bastar Craton of India. The H2S2 was likely in situ enclosed by the host rubies rather than a reaction product that formed during the cooling of H2S and S8, suggesting sulfanes are stable at elevated temperatures (e.g., >600 °C). By comparing the lithologies and metamorphic conditions of these two sulfane-bearing cases (Bastar and Yuanjiang), it is suggested that amphibolite facies metamorphism of sedimentary sequence that deposited in a continental platform setting might favor the generation of sulfanes. Sulfanes may play an important role in the mobilization of Cr that is essential for ruby crystallization.